Modeling of CNT-reinforced nanocomposite with complex morphologies using modified embedded finite element technique. (1st November 2019) - Chen, X.; Alian, A.R.; Meguid, S.A.
Abstract: In this article, we overcome the limitations of traditional finite element (FE) method in modeling CNT-reinforced nanocomposites with complex morphologies by developing a modified embedded finite element (mEFE) method. The composite constituents in the mEFE model are discretized independently but simulated simultaneously as a coupled system. The major advantage of this approach is discretizing the matrix as a regular grid, irrespective of the complex nature of the CNT network. The developed modeling approach allowed us to simulate realistic representative volume elements (RVEs) containing randomly dispersed CNTs of different curvatures, orientations, aspect ratios and volume fractions. An advanced Monte Carlo based algorithm was also developed to generate complex CNT networks. The proposed mEFE method requires a significantly shorter preprocessing effort and is more computationally efficient when compared to traditional FE method. It allowed us to study large scale RVEs reinforced with high CNT concentrations. The results of this idealised case showed that the elastic modulus of the nanocomposite increases with increasing the volume fraction of the CNTs; reaching 200 % improvement at 5 % volume fraction. However, the enhancement in the properties was not obvious at higher concentrations due to the poor dispersion and agglomeration of the dispersed CNTs.